Synthesis of AI-MCM-41/ZSM-5 composite for oxidation of norbornene to norbornene oxide - Faridah Abu Bakar, 1985-; Salasiah Endud; Fakulti Sains (2010)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2010